Democratic orientations of the people in the South Caucasus in the mid- 1990s (Journal of Philosophy Culture and Political Science, 2019)
Favorable attitudes toward democratic values held by ordinary citizens, or lack of it, have long been considered as an important factor in explaining the prospects for the democratization process. Drawing upon the third wave (1995-1998) of the World Values Survey project, this paper comparatively explores the democratic attitudes of the people in the South Caucasus region (Azerbaijan, Armenia and Georgia) in the mid-1990s. Theoretical justification for analyzing mass orientations is grounded in the basic assumption that what people think and how they view democracy is crucial to understanding the possibilities for change and reform. The results reported here carry a positive claim and suggest that democratic orientations appear to be a shared desire in all three nations with small variations. The empirical evidence presented below may also indicate that the values and beliefs of mass publics do not seem to be an obstacle to the future democratization in the region.Key words: South Caucasus, Azerbaijan, Georgia, Armenia, Democracy, Democratic Values, Politics, and Political Participation.